BENGKEL MOTOR CUSTOM - Felix Halim; Stephanus Huwae (Jurusan Arsitektur dan Perencanaan, 2019)
A motor custom is a motorcycle that is made/modified based on buyer needs, user, or a particular individual’s specification. Motorcycle originally functioned as a means of transportation from one point to another, yet it has now evolved into a new kind of lifestyle. This phenomenon emerged as an impact of changes in the society’s pattern of needs, going from basic needs into leisure needs. The milenial generation’s basic needs were mostly fulfilled; therefore, according to The Maslow Theory, the generation is now in the next stage which is psychological needs. Creative economy has become the backbone of Indonesia’s economy. The government’s support towards creative industries through Bekraf is a positive sign to provide a space for motorcycle enthusiasts to produce motor custom les in Indonesia. To start a workshop business, they need network, tools, and a place. Economic incubator can help start-ups to open Motor Custom Workshop by providing their need. Sharing tools offer start-ups with equipment that they can use together, helping start-ups to start their business without having to spend a lot of capital buying their own equipment. Motor Custom Workshop is located in Kemang, where motorcycle communities are often found on the streets, on their Sunmori. This phenomenon is recorded and incorporated into design by using Pattern Language method, which is able to strengthen the link between program and the surroundings. From the phenomena and theories reviewed, it can be concluded that Motor Custom Workshop for Milenials is a potential business venture. Motor Custom Workshop offers opportunity for motorcycle enthusiasts hoping to delve in this business to gain experience in assembling and modifying motorcycles with available rental tools. Motor Custom Workshop is expected to promote Indonesia’s creative industry, bring out innovative products, educate the public about automotif, and increase the appeal of local product.AbstrakMotor Custom adalah motor yang dibuat/ diubah sesuai dengan kebutuhan pembeli, pengguna, atau sepesifikasi individu tertentu. Perubahan fungsi motor yang semula merupakan alat transportasi dari satu titik ke titik lain, sekarang bertambah menjadi suatu gaya hidup/lifestyle. Fenomena ini muncul sebagai imbas perubahan pola kebutuhan masyarakat dari basic needs menjadi leisure needs. Generasi Milenial basic needs sudah terpenuhi, maka generasi Milenial menurut Teori Maslow berada di tingkat selanjutnya yaitu di tahap psychological needs. Ekonomi kreatif menjadi tulang punggung perekonomian Indonesia. Dukungan pemerintah akan industri-industri kreatif melalui Bekraf (Badan Ekonomi Kreatif) merupakan tanda positif untuk membuat wadah pembuatan motor custom di Indonesia. Untuk memulai usaha bengkel mereka membutuhkan network, tools, dan wadah/ tempat. Bengkel Motor Custom dapat membantu start-up untuk membuka Bengkel Motor Custom dengan cara memberikan kebutuhan mereka. Sharing tools dapat meringankan dalam memulai usaha bengkel mereka, dikarenakan usaha yang mereka jalankan memiliki tools yang digunakan secara bersama-sama dengan start-up lainnya. Bengkel Motor Custom berada di daerah Kemang, dimana fenomena motor riding bersama sering ditemukan ketika Sunday Morning Ride. Fenomena tersebut direkam dan dituangkan ke dalam desain menggunakan metode Pattern Language, yang dapat membuat keterkaitan antara program dengan lingkungan menjadi kuat. Dari fenomena dan teori yang telah dikaji dapat dilihat bahwa peluang Bengkel Motor Custom untuk Milenial cukup sesuai. Bengkel Motor Custom dapat memberikan pengalaman merakit dan memodifikasi motornya juga dapat dilakukan sendiri dengan memakai tools yang direntalkan. Tujuan dari hadirnya Bengkel Motor Custom untuk memajukan industri kreatif Indonesia, mampu memunculkan produk yang inovatif, serta dapat mengedukasi masyarakat luas tentang otomotif dan meningkatkan daya tarik akan produk lokal.